ANALISIS KELAYAKAN FINANSIAL USAHA PENANGKAPAN IKAN MENGGUNAKAN PANAH DAN BUBU DASAR DI PERIRAN KARIMUNJAWA - Pratama, Ficka; Boesono, Herry; Hapsari, Trisnani (Journal of Fisheries Resources Utilization Management and Technology, 2012)
Karimunjawa is an Archipelago with good coral and abundant reef fish production. One of fishing gears that used in catch reef fish is spear gun and bottom traps. The using of compressor by spear gun is judged dangerous, so bottom traps is an alternative for catch the reef fish without using compressor. The objective of this research is to analysis feasibility of fishing effort with spear gun and bottom traps that is saw from financial aspect. Sampling method that used is snowball sampling, with number of the sample is 30 respondent. The data taking in this research is trough interview and observation. In this research is found that economic aspect of spear gun effort needs IDR34.696.500 of financial capital, total cost IDR204.546.920, income IDR237.733.500, profit IDR33.186.580. Bottom Traps effort needs capital financial IDR45.488.333, total cost IDR208.525.402, income IDR258.497.000, profit IDR49.971.598. Base on financial analysis on Spear Gun, found that the NPV’s value is IDR216.790.754, IRR 92%, B/C Ratio 1,16, ROI 95%, Payback Period is 1 year and Profitability Index is 6,2. Whereas the Bottom Traps found that the NPV’s value is IDR313.828.168, IRR 101%, B/C Ratio 1,23, ROI 110%, Payback Period is 0,91 year and Profitability Index is 6,9. The conclusion from this research is bottom traps has more suitable than spear gun.